Factors affecting the housing problem in the Hurriya neighborhood - Jawdat, Nada Shaker; Jasim, Amany Mouaed (Al-Adab Journal, 2015)
The study tackles the topic of residence problem in Al-Hurriya city which represents one of the biggest Shu’la municipality neighborhoods, in order to shed the light on the residential problem and the factors causing it and identify the residential and the population reality so as to know the size of population deficiency and crowdedness to find the treatments and provide proposals which will limit the increasing demand manner on residential units. The study area saw an architectural expansion due to the increasing number of population and the emergence of new residential quarter, which motivated them to search for more lands to build residential units instead of living in old residential quarters established ,. Today, Al-Hurriya city suffers from a collection of problems .. A group of factors appeared through which the direct cause of the residential problem was defined at the study area. There were several causes behind the residential problem, the most important of which were the small area of residential units, small number of the units bedrooms, high occupation rate of units whether by individuals or families, low rate of family monthly income, low living level which lessens the chances of maintenance and reconstruction for those units, thus decreasing their assumed age, with the impact variance of those variables from one quarter to another at the study area